2007
DOI: 10.1103/physrevb.76.165124
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Verwey transition in magnetite: Group theory, electronic structure, and lattice dynamics study

Abstract: The Verwey phase transition in magnetite has been analyzed using the group theory methods. It is found that two order parameters with the symmetries X3 and ∆5 induce the structural transformation from the high-temperature cubic to the low-temperature monoclinic phase. The coupling between the order parameters is described by the Landau free energy functional. The electronic and crystal structure for the cubic and monoclinic phases were optimized using the ab initio density functional method. The electronic str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 98 publications
(191 reference statements)
5
61
2
Order By: Relevance
“…23: It is a result of local destruction of electronic order induced by secondary excitations. We note that the structural relaxation, which is expected to occur on times of 105 fs and 65 fs, 28,29 is not observable in our data, e.g., as a second time scale. In an earlier experiment, we found that when probing the (0 0 12) peak at the Fe- L 2,3 resonance, i.e., when sensitive to electronic order like in the present experiment, structural relaxation is visible as a shift of the peak position on the detector 23 .…”
Section: Data Analysis and Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…23: It is a result of local destruction of electronic order induced by secondary excitations. We note that the structural relaxation, which is expected to occur on times of 105 fs and 65 fs, 28,29 is not observable in our data, e.g., as a second time scale. In an earlier experiment, we found that when probing the (0 0 12) peak at the Fe- L 2,3 resonance, i.e., when sensitive to electronic order like in the present experiment, structural relaxation is visible as a shift of the peak position on the detector 23 .…”
Section: Data Analysis and Discussioncontrasting
confidence: 55%
“…Indeed, sub-300 fs structural dynamics have also been found in other transition-metal oxides 26,27 . For the structural part of the Verwey transition, the dominant Δ 5 und X 3 phonons 28,29 allow us to estimate a structural relaxation time, which we assume to be at least of the order of one quarter of their phonon oscillation period, yielding 105 fs and 65 fs, respectively 30 . These time scales also define the temporal resolution needed to observe dynamical decoupling.…”
Section: Introductionmentioning
confidence: 85%
“…Different U eff values have been proposed for Fe 3 d orbitals in different materials ( e.g . a much larger U eff value of 3.2 eV was used for magnetite31). The U eff value is also dependent on the exchange correlation functional used32.…”
mentioning
confidence: 99%
“…Despite the fact that this structure is only a first approach, accounting for only a quarter of the actual cell, recent calculations still use it to explain the Verwey transition within a scheme of pseudo-Fe 2+ /Fe 3+ charge and orbital orderings. [14][15][16][17][18] To sum up, the lack of an accurate determination of the magnetite structure below T V has obviated a reliable characterization of the CO developed at the metal-insulator transition, if any. This is because of the enormous difficulty involved in solving its crystal structure at low temperature.…”
Section: Introductionmentioning
confidence: 99%